Exogenous melatonin delays gastric emptying rate in rats: role of CCK2 and 5-HT3 receptors - (:unkn) unknown (My University, 2005)
Pineal hormone melatonin is proposed as a potential treatment for severe sleep disturbances, and various gastrointestinal disorders. It was shown that melatonin increases intestinal motility and influences the activity of myoelectric complexes of the gut. The aim of the study was to evaluate the mechanisms of the effect of exogenous melatonin on gastric emptying rate. Male Sprague-Dawley rats were fitted with gastric cannulas under anesthesia. The rate of gastric emptying of saline was determined after instillation into the gastric fistula, from the volume and phenol red concentrations recovered after 5 min. Melatonin injected intraperitoneally (ip; 0.001-100 mg/kg) delayed gastric emptying rate of saline at 3 and 10 mg/kg doses. When administered ip 15 min before melatonin (10 mg/kg) injections, CCK2 (L-365,260, 1 mg/kg) or 5-HT3 receptor (ramosetrone, 50 microg/kg) blockers abolished melatonin-induced delay in gastric emptying rate, while the blockade of sympathetic ganglia (bretylium tosylate, 15 mg/kg) significantly reduced the delay in gastric emptying rate. CCK1 receptor blocker (L-364,718, 1 mg/kg) had no significant effect on the delaying action of melatonin. Our results indicate that pharmacological doses of melatonin delay gastric emptying via mechanisms that involve CCK2 and 5-HT3 receptors. Moreover, it appears that exogenous melatonin inhibits gastric motility in part by activating sympathetic neurons.
Keywords: Animals; Male; Rats; Melatonin; Dose-Response Relationship, Drug; Rats, Sprague-Dawley; Capsaicin; Gastric Emptying; Vagus Nerve; Receptors, Serotonin, 5-HT3; Gastrointestinal Tract; Benzodiazepinones; Phenylurea Compounds; Neurons, Afferent; Receptor, Cholecystokinin B; Ganglia, Sympathetic; Benzimidazoles; Adrenergic Antagonists; Autonomic Nerve Block; Bretylium Tosylate; Serotonin 5-HT3 Receptor Antagonists